A Determination of fracture toughness in plain concrete specimens by R curve (Fracture and Structural Integrity, 2019)
Since the last two centuries, concrete has become the number one building material in the world. Therefore, we are interested in studying the mechanical behavior at failure of this material and calculate its toughness.In this paper, we trace the R-curve to determine the critical stress intensity factor and the crack evolution by specifying the three stages:  crack stopping stage, stable propagation stage and an unstable propagation stage. The R-curve was obtained from the curve connecting the crack mouth opening to the applied load for prismatic specimens normalized by ASTM and notched laterally (SENB). These specimens are made from concrete with 25 MPa compressive strength and subjected to three-point bending. The dimensionless ratio of the initial notch length and the specimen width is between 0.3 and 0.6.During loading, we can observe an elastic deformation followed by a significant plastic deformation, the average value of the critical stress intensity factor found is 1.05 MPa.m1/2.
Keywords: Toughness; R-curve; CMOD; SENB; Three-point bending